2004
DOI: 10.1073/pnas.0402959101
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson's disease protein DJ-1 is neuroprotective due to cysteine-sulfinic acid-driven mitochondrial localization

Abstract: Loss-of-function DJ-1 mutations can cause early-onset Parkinson's disease. The function of DJ-1 is unknown, but an acidic isoform accumulates after oxidative stress, leading to the suggestion that DJ-1 is protective under these conditions. We addressed whether this represents a posttranslational modification at cysteine residues by systematically mutating cysteine residues in human DJ-1. WT or C53A DJ-1 was readily oxidized in cultured cells, generating a pI 5.8 isoform, but an artificial C106A mutant was not.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
1,064
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,017 publications
(1,117 citation statements)
references
References 33 publications
(55 reference statements)
44
1,064
1
8
Order By: Relevance
“…While Zhang et al. reported that DJ-1 is located in the mitochondrial matrix and intermembrane space [24], Canet-Aviles et al reported that DJ-1 is located in the outer membrane but not inside of mitochondrial outer membrane [11]. Although the reasons for this discrepancy are not clear, different cells and methods used to identify the localization of DJ-1 might have given rise to the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While Zhang et al. reported that DJ-1 is located in the mitochondrial matrix and intermembrane space [24], Canet-Aviles et al reported that DJ-1 is located in the outer membrane but not inside of mitochondrial outer membrane [11]. Although the reasons for this discrepancy are not clear, different cells and methods used to identify the localization of DJ-1 might have given rise to the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…DJ-1 was first identified by our group as a novel oncogene product [1] and was later found to be a causative gene product of a familial form of PD, PARK7 [2]. DJ-1 plays roles in transcriptional regulation [3][4][5][6][7][8] and anti-oxidative stress reaction [9][10][11][12], and loss of its function is thought to affect the onset of PD. DJ-1 has three cysteines at amino acid numbers 46, 53 and 106 (C46, C53 and C106, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PARK7 is localized in the cytoplasm and the nucleus; it has also been shown that some PARK7 is localized in the mitochondria [9,10,19,20]. Several lines of evidence suggest that PARK7 is secreted from cells into the circulation despite the fact that PARK7 lacks a secretory signal sequence [21–29].…”
Section: Introductionmentioning
confidence: 99%